The new reality: casanareños microentrepreneurs after the first year of COVID-19. Diagnostic instrument, impact analysis and identification of innovative strategies for the recovery of the sector. - Gonzalez Villar, Armando
The Project seeks to generate innovation, research and technological development for the Centro Agroindustrial y Fortalecimiento empresarial de Casanare SENA, the educational community, the microentrepreneurs of the región and the community, through the elaboration of the diagnosis that allows us to characterize the microenterprise sector of the urban and rural área of the Departament, and identify the main effects on sales and employment, in the fase of the Covid-19 contingency, and its impact generated in the micro-bussiness one year after its coexistence with said contingency, taking into account that for economic reactivation essentially requires concrete strategies that manage to increase working capital, and the adoption of flexible, modern and adapted business models in the microenterprise sector as the main source of employment.